Analisis Penerapan Akuntansi Biaya Operasional Pada Usaha Kerupuk Goreng Pak Wayan Kecamatan Kolaka - Yulia Putri Dewanti; Arnadi Chairunnas; Nichen . (CV. ITTC INDONESIA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the regional economy, creating jobs, and improving community welfare. However, many have not yet implemented operational cost accounting optimally, resulting in inadequate cost information for effective decision-making. This study aims to analyze the implementation of operational cost accounting at Pak Wayan Fried Crackers MSME in Kolaka District. This study uses a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation with the business owner as the primary informant. This study also identifies production cost components consisting of raw material costs, direct labor costs, and factory overhead costs as the basis for calculating the Cost of Goods Sold (COGS). The collected data were analyzed through data reduction, data presentation, and conclusion drawing based on cost accounting theory. The results of the study indicate that the implementation of cost accounting has been carried out simply but not optimally. The owner has calculated the Cost of Goods Sold (COGS), but the recording is still manual and unstructured. The COGS of a product with a selling price of Rp1,000 is Rp944 per pack, while the product with a selling price of Rp2,000 is Rp682 per pack. The total profit obtained is Rp1,166,400. A product with a price of Rp2,000 provides a larger profit margin than a product with a price of Rp1,000, so it has the potential to be a more profitable product for the business. The main obstacles include fluctuations in standard language prices, difficulties in allocating indirect costs, limited accounting knowledge, and the absence of structured financial reports. This study concludes that the implementation of operational cost accounting in businesses still needs to be improved through a more systematic recording system to support efficiency and accuracy of decision making.